Correlation between Optic Nerve Sheath Diameter, Rotterdam Computed Tomography Score, and Glasgow Coma Scale in Head Injury - Febrina, Debora; Lubis, Netty Delvrita; Arsyad, Abdurrahman Mousa (Jurnal Kedokteran Brawijaya, 2025)
Increased intracranial pressure (ICP) is one of the fatal events resulting from head injury. The gold standard for diagnosing elevated ICP, external ventricular drainage (EVD), is highly invasive, unavailable in the initial assessment, and contraindicated in some patients. Optic nerve sheath diameter (ONSD) has recently emerged as a non-invasive alternative for ICP monitoring. The Rotterdam CT Score (RCTS) assesses basal cisterns, midline shift, epidural mass lesion, and intraventricular hemorrhage (IVH) and/or traumatic subarachnoid hemorrhage (tSAH) on head CT scan. High RCTS is associated with higher mortality. Clinically, it can be assessed from level of consciousness with the Glasgow Coma Scale (GCS). This cross-sectional study aims to analyze the correlation between ONSD, RCTS, and GCS in head injury patients who underwent non-contrast head CT scans at the Radiology Department of Adam Malik Hospital, Medan from May 1, 2022, to April 30, 2023. ONSD and RCTS on initial CT scan were measured by two examiners, and GCS scores were obtained from the medical record. From 42 patients, the mean ONSD was 6.26±0.80mm, the median RCTS was 3 (range: 1 to 6), and the median GCS was 14 (range: 3 to 15). There is a significant strong positive correlation between ONSD and RCTS (r=0.747) and a moderate negative correlation between ONSD and GCS (r=-0.476), with p<0.05. The larger the ONSD on the initial head CT scan, the higher the Rotterdam CT score and the lower the GCS score.